1999
DOI: 10.1590/s0036-46651999000300007
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of toxoplasmosis in Fortaleza, Ceará, Brazil

Abstract: SUMMARYA serological survey of Toxoplasma gondii infection in population groups in Fortaleza, Brazil, was conducted, in order to identify seroprevalence rates according to age and risk factors associated with acquired infection. A Toxoplasma IgG-antibody enzyme immunoassay (Sanofi Pasteur Diagnostics, Marnes la Coquette, France) was employed to assess the immunity. Public day-care centers and schools were randomly selected, while three large antenatal clinics and maternity units were choosen by its importance.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
15
1
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 13 publications
6
15
1
2
Order By: Relevance
“…These observations agree with previous studies that indicate a percentage of IgG anti-T. gondii antibodies in the Brazilian population (20,(23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Discussionsupporting
confidence: 93%
“…These observations agree with previous studies that indicate a percentage of IgG anti-T. gondii antibodies in the Brazilian population (20,(23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Discussionsupporting
confidence: 93%
“…6 In the present study more than 60% of the pregnant women tested positive for IgG anti-T. gondii antibodies, which is in agreement with other studies carried out in Brazil reporting seropositivity rates ranging from 22.8% to 71.5%. [7][8][9][10][11][12] Two recent studies performed in the northwest region of São Paulo State found rates similar to those reported in the current study. 5,13 Pregnant women at risk of congenital transmission of toxoplasmosis were younger than those without risk.…”
Section: Discussionsupporting
confidence: 91%
“…In Brazil, several descriptive studies show different serologic seroprevalences: in the mid-west and north, 54 and 75% respectively [9]; 80.4% in an indigenous group in the state of Mato Grosso [10] and from 66 to 75% in rural populations in the south (state of Paraná) [11]; from 77.5 to 58.9% soroprevalence among pregnant women in an urban region of São Paulo [12]; from 23 to 84% in Campos dos Goytacazes (northern Rio de Janeiro State, in the Brazilian southeast) [13] and 68.4% among primary school students in the city of Rio de Janeiro [14]. A progressive rise in seropositivity with age has been seen in children, adolescents and pregnant women in Fortaleza (northeast Brazil), ranging from 22.8 to 71.5% [15]; also in the Northeast, in the city of Recife, a seroprevalence of 79% for men and 63.4% for women was found among blood donors [16]. The increase in incidence of toxoplasmosis has shown to be proportional to age, with an estimated rate of serological conversion of 10% among 0-5 year-olds, 1% among 6-20 year-olds, and 0.3% for people above 20 years old [3].…”
mentioning
confidence: 98%